Exploration of The Neutrophil-to-Lymphocyte Ratio as an Indicator of Inflammation with Hemoglobin and Creatinine Levels as an Illustration of Kidney Function in Tuberculosis Cases - Christina Destri Wiwis Wijayanti; Waode Fifin Ervina Muslihi; Herin Mawarti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Tuberculosis (TB) remains a major global health challenge, consistently ranking among the leading causes of morbidity and mortality worldwide. Its chronic progression, ease of airborne transmission, and potential to induce systemic inflammation and multi-organ involvement underscore the urgency of timely diagnosis and monitoring of disease progression and treatment response. In this context, the neutrophil-to-lymphocyte ratio (NLR) has emerged as a simple and cost-effective biomarker of systemic inflammation. This study aimed to investigate the association between NLR and two key clinical parameters, haemoglobin and creatinine levels, as indicators of anemia and renal function, respectively, in TB patients. A descriptive analytical observational study with a cross-sectional design was conducted at the Immunology Laboratory of the Faculty of Health Sciences, Maarif Hasyim Latif University, from August 2024 to January 2025. The study sample comprised 80 adult TB patients, and data were analyzed using Spearman's rank correlation via SPSS version 25. Results revealed a statistically significant weak negative correlation between NLR and hemoglobin levels (p = 0.040, r = -0.230), suggesting that heightened inflammation may be associated with lower hemoglobin levels, potentially due to inflammation-induced anemia. In contrast, the correlation between NLR and creatinine levels was not statistically significant (p = 0.303, r = 0.117), indicating a weak and clinically inconclusive relationship between systemic inflammation and renal function in patients without evident kidney disorders. These findings underscore the potential utility of NLR as an early marker of inflammation-related anemia in TB patients. However, NLR alone may be insufficient for assessing renal function, highlighting the need for complementary diagnostic parameters in future research. Overall, NLR offers promise as a clinical evaluation tool in TB management, particularly in resource-limited settings. Keywords: Neutrophil-to-Lymphocyte Ratio (NLR), Tuberculosis, Inflammatory Biomarkers, Anemia, Kidney Function.